The Legal and Tax Dimension of Metaverse - Ceyda Kükrer (Maliye Çalışmaları Dergisi)
Human life changes as technology advances. The virtual universe, also known as the metaverse, is the final transition point. Unlike previous work on the Metaverse based on Second Life, the current Metaverse is based on the social values of Generation Z, with no distinction between the online and offline self. Despite the fact that Second Life is a virtual world, it has attracted significant investment and has emerged as an important venue for the marketing and branding of real-world products and services. In contrast to the previous Metaverse, integrating advanced social activities and neural network methods has necessitated a new definition for Metaverse, which is appropriate for today. In this context, the current study focuses on the Metaverse field’s expectations and concerns and its legal and tax implications. At the same time, the study will highlight the concept of the Metaverse and its relationship to the concept of the virtual world. The article also examines the legal dimensions of virtual items,primarily by looking at global practices and examples in Türkiye. The metaverse taxation process will be explained in light of the US virtual world tax decisions by considering the experiences with Second Life.